Rekonstruksi Rekrutmen Calon Legislatif Perempuan: dari Pendekatan Formalistik menuju Substantif - Redhani, Muhammad Erfa; Erlina, Erlina (Jurnal Hukum IUS QUIA IUSTUM, 2026)
The evolution of Constitutional Court decisions indicates a gradual strengthening of the 30% quota for women in legislative candidacy, including the emphasis on sanctions for non-compliance. However, this strengthening is not necessarily directly proportional to the quality of women's representation in practice, since political parties often conduct short-term and formalistic recruitment simply to fulfill candidacy requirements. This article fills a gap in previous researches by analysing Constitutional Court Decision No. 128/PUU-XXIV/2026 as a basis for evaluating political parties' obligations to meet the women's partitcipation quota. This article addresses two main issues: the development of Constitutional Court decisions in strengthening the quota for women legislative candidates in Indonesia and the design of strengthening women's candidate recruitment to prevent the practice of merely formal representation. This is a normative legal study using legislative, conceptual, and case study approaches. Legal materials were collected through literature review, then analysed descriptively and qualitatively. The results show that the development of Constitutional Court decisions has been progressive, starting from the legitimacy of affirmative action, strengthening women's representation in political structures, to affirming the legal consequences for political parties' non-compliance. However, the effectiveness of quota policies remains dependent on the recruitment design within political parties. Therefore, this article suggests that recruitment of female legislative candidates should be directed not only at meeting quotas but also at sustainable cadre development, open selection, and adequate political development so that women emerge as competent and substantive political actors in the legislative process and public policymaking.